2018
DOI: 10.1016/j.fct.2017.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to permethrin promotes high fat diet-induced weight gain and insulin resistance in male C57BL/6J mice

Abstract: Permethrin is a pyrethroid pesticide that was previously reported to promote fat accumulation and insulin resistance in vitro. A recent study in female mice also found that permethrin could promote high fat-induced insulin resistance. The effects of permethrin on glucose and lipid metabolisms in male mice, however, remain unknown. The purpose of this study was to investigate the effects and interactions of permethrin exposure (50, 500, and 5000 μg/kg body weight/day) and dietary fat (low fat, 4% w/w; high fat,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 64 publications
5
33
1
Order By: Relevance
“…Prospective observational studies in adults have shown that an organic diet reduces the risk of being overweight or obese, but the evidence is inconclusive due to likely residual confounding, as consumers of organic food tend to have overall healthier lifestyles [3]. Several animal models suggest the implication of pyrethroid and neonicotinoid pesticides with oxidative stress and inflammation phenomena (OSI) [4,5] and adiposity/weight gain [6,7]. Some human studies have found associations between exposure to other pesticides (organophosphates) and oxidative stress [810].…”
Section: Introductionmentioning
confidence: 99%
“…Prospective observational studies in adults have shown that an organic diet reduces the risk of being overweight or obese, but the evidence is inconclusive due to likely residual confounding, as consumers of organic food tend to have overall healthier lifestyles [3]. Several animal models suggest the implication of pyrethroid and neonicotinoid pesticides with oxidative stress and inflammation phenomena (OSI) [4,5] and adiposity/weight gain [6,7]. Some human studies have found associations between exposure to other pesticides (organophosphates) and oxidative stress [810].…”
Section: Introductionmentioning
confidence: 99%
“…Leptin was also increased in offspring with less glucose tolerance. Serum leptin is correlated with body fat mass in humans 37 and mice, 38 supporting the notion of differences in body composition. This marker could also indicate a decreased appetite in MNR offspring, particularly in those with glucose intolerance.…”
Section: Discussionmentioning
confidence: 62%
“…Given this limited data set, the doses used in the current study may not be achievable. Nevertheless, the effects of obesogens can be aggravated by dietary fat intake as previous studies have shown the interaction between obesogens treatment and dietary fat (Xiao et al 2017, Sun, Xiao et al 2016, Sun et al 2017, Xiao et al 2018).…”
Section: Discussionmentioning
confidence: 99%